Lexicographic Tools. A Coursebook - Caballero Rodríguez, Mª del Rosario (MANUALES DOCENTES, 2016)
Lexicographic tools are important when learning a language. With their help, you can look up words and explore their spelling(s) and pronunciation(s), their meaning(s), how they translate into other languages, their syntactic properties, and how people use them. Of course, in order to use lexicographic tools effectively you need to make several decisions and think about. In other words, you must learn how to find information accurately and quickly and which tool you need to use in order to achieve your goals. You may also need to use several tools. This means you need to be open-minded and, above all, must learn how to combine the tools at your disposal to make the most of them. For instance, imagine you need to know how to use the verb realize.